Plasma Imaging, LOcal Measurement, and Tomographic Experiment (PILOT): A Mission Concept for Transformational Multi-Scale Observations of Mass and Energy Flow Dynamics in Earth’s Magnetosphere - Malaspina, David; Ergun, Robert; Goldstein, Jerry; Spittler, Constance; Andersson, Laila; Borovsky, Joseph; Chu, Xiangning; De Moudt, Lauren; Gallagher, Dennis; Jordanova, Vania; Lejosne, Solène; Link, Jason; et al. (Frontiers in Astronomy and Space Sciences, 2022)
We currently do not understand the fundamental physical processes that govern mass and energy flow through the Earth's magnetosphere. Knowledge of these processes is critical to understanding the mass loss rate of Earth's atmosphere, as well as for determining the role that a planetary magnetic field plays in atmospheric retention, and therefore habitability, for Earth-like planets beyond the solar system. Mass and energy flow processes are challenging to determine at Earth in part because Earth's planetary magnetic field creates a complex `system of systems' composed of interdependent plasma populations and overlapping spatial regions that perpetually exchange mass and energy across a broad range of temporal and spatial scales. Further, the primary mass carrier in the magnetosphere is cold plasma (as cold as $\sim$0.1 eV), which is invisible to many space-borne instruments that operate in the inner magnetosphere. The Plasma Imaging LOcal and Tomographic experiment (PILOT) mission concept, described here, provides the transformational multi-scale observations required to answer fundamental open questions about mass and energy flow dynamics in the Earth's magnetosphere. PILOT uses a constellation of spacecraft to make radio tomographic, remote sensing, and in-situ measurements simultaneously, fully capturing cold plasma mass dynamics and its impact on magnetospheric systems over an unprecedented range of spatial and temporal scales. This article details the scientific motivation for the PILOT mission concept as well as a potential mission implementation.